Modulation of human multidrug-resistance MDR-1 gene by natural curcuminoids - P. Limtrakul (2018)
Multidrug resistance (MDR) is a phenomenon that is often associated with decreased intracellular drug accumulation in patient's tumor cells resulting from enhanced drug efflux. It is related to the overexpression of a membrane protein, Pglycoprotein (Pgp-170), on the surface of tumor cells, thereby reducing drug cytotoxicity. A variety of studies have tried to find MDR modulators which increase drug accumulation in cancer cells. In this study, natural curcuminoids, pure curcumin, demethoxycurcumin and bisdemethoxycurcumin isolated from turmeric (Curcuma longa Linn.) were compared for their potential ability to modulate the human MDR-1 gene expression in multidrug resistant human cervical carcinoma cell line, KB-V1. Western blot analysis and RT-PCR showed that all the three curcuminoids inhibited MDR-1 gene expression and bisdemethoxycurcumin produced maximum effect. In additional studies we found that commercial grade curcuminoid (approximately 77% curcumin, 17% demethoxycurcumin and 3% bisdemthoxycurcumin) decreased MDR-1 gene expression in a dose dependent manner and had about the same potent inhibitory effect on MDR-1 gene expression as our natural curcuminoid mixtures. These results indicate that bisdemethoxycurcumin is the most active of the curcuminoids present in turmeric for modulation of MDR-1 gene. Treatment of drug resistant KB-V1 cells with curcumin increased their sensitivity to vinblastine, which was consistent with a decreased MDR-1 gene product, a P-glycoprotein, on the cell plasma membrane. Although many drugs that prevent the P-glycoprotein function have been reported, this report describes the inhibition of MDR-1 expression by a phytochemical. The modulation of MDR-1 expression may be an attractive target for new chemosensitizing agents. © ISHS 2005.